2014
DOI: 10.12944/carj.2.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Economic Assessment of R ural Women Participation in Processing and Marketing of Soybean in Tarka LGA of Benue State Nigeria

Abstract: The study was carried out in four markets namely: Wanune, Asukunya, Tiortyu and Gwarche markets from which 109 women processors and marketers were sampled. Structured questionnaires were used to elicit relevant information from the women. The first objective described the socio-economic characteristics of processors and marketers of soybean in the study area; the second identified the different forms of soybean product in the study area; the third determined the level of rural women participation in the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…This is expected since wholesale business requires risk which can be well managed by mature mind. This result agreed with Ezihe et al (2014) who found that majority (97.3%) of soybean processors are within the active age of between 21 and 60 years with average age of 37 years and Uwaoma (2015) who found the average age of soybean processor in Anambra State, Nigeria to be 43 years. 75.7% of soybean small-scale processors and 59.5% of retailers were female.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This is expected since wholesale business requires risk which can be well managed by mature mind. This result agreed with Ezihe et al (2014) who found that majority (97.3%) of soybean processors are within the active age of between 21 and 60 years with average age of 37 years and Uwaoma (2015) who found the average age of soybean processor in Anambra State, Nigeria to be 43 years. 75.7% of soybean small-scale processors and 59.5% of retailers were female.…”
Section: Resultssupporting
confidence: 89%
“…This result implied that the marketers can get frequent productive advice, assistance and support from their spouse. This finding also corroborates Ezihe et al (2014) who found that most (67.9%) of soybean marketers in Tarka LGA of Benue state, Nigeria were married and Uwaoma (2015) who also found that 91% of soybean processors in Anambra State, Nigeria were married.…”
Section: Resultssupporting
confidence: 85%
“…In communities where traditional values hinder women's empowerment, re-engineering their mindset, ideologies, and perceptions can create opportunities for them. Women play a significant role in agricultural production and household food security (Ezihe et al, 2014).…”
Section: Empowering Minds and Transforming Agriculture: Youth-focusedmentioning
confidence: 99%
“…Marital status is also a crucial factor in the farming profession. A high proportion of married respondents suggest an additional supply of labor from the family (Ezihe, Agbugba and Iornum, 2014). In view of this study, data was collected on the marital status of smallholder maize farmers, and Table 3 presented the results.…”
Section: Marital Status Distribution Of the Household Headsmentioning
confidence: 99%
“…In essence, the use of family labor helped reduce the cost that would have been spent on hired labor. The implication of this is that more cost will be incurred due to more hired labor employed to supplement the family labor (Ezihe et al, 2014). Table 5 indicated that the number of years spent in maize farming is an important factor as it relates to the farmers' experience, and will in turn reflect the effectiveness of an agro-enterprise in order to yield a reasonable output.…”
Section: Household Size Distribution Of the Farmersmentioning
confidence: 99%